Land Uses Simplified Index (LUSI): Determining Land Pressures and Their Link With Coastal Eutrophication - Flo, Eva; Garcés, Esther; Camp, Jordi (Frontiers in Marine Science, 2019)
Human activities on land result in the high-level production of nutrients. When these nutrients reach coastal waters, they could drive the eutrophication process. Here we present the Land Uses Simplified Index (LUSI), an easy-to-use tool for assessing continental pressures on coastal waters. This assessment is done by indirectly estimating continental nutrient loads and concentrations and their influence on coastal waters. LUSI is based on systematic information describing both the land uses that influence coastal waters by providing nutrient-rich freshwater inflows (urban, industrial, agricultural, and riverine) and the coastline morphology, which can modify this influence, as it determines the degree of coastal water confinement and therefore the likelihood that these inflows will be diluted. A low LUSI value indicates that coastal waters are not or only slightly influenced by continental pressures and/or that these pressures are diluted. On the contrary, a high LUSI value indicates that coastal waters are strongly influenced by continental pressures and/or that these pressures are not diluted. LUSI fulfils a methodological gap, as a simple method to assess coastal pressures when there is a lack of information. Furthermore, it fulfils the requirement of the Water Framework Directive for a true pressure assessment (i.e. not confounded with impact), which for coastal waters imply using pressure data from land. An additional and important feature of LUSI is that it allows the establishment of pressure-impact relationships with impact indicators, such as those related to the Biological Quality Elements of the above Directive. For example, a relationship based on LUSI, as a proxy of pressure, and on the chlorophyll-a concentration, as a proxy of phytoplanktonic biomass and, thus, of the eutrophication impact. By providing insights into the land uses that trigger eutrophication in coastal waters, LUSI aids in the design of measures aimed at remediating anthropogenic damage caused to the environment.